The Speech, Spatial, and Qualities of Hearing Scale for Parents of Children with Impaired Hearing, SSQ-P: Swedish translation ... - Erixon, Elsa; Mäki-Torkko, Elina; Löfkvist, Ulrika (figshare, 2024)
The Speech, Spatial, and Qualities of Hearing Scale for Parents of Children with Impaired Hearing, SSQ-P: Swedish translation The SSQ-P Scale is an adaption of the original SSQ developed for adults by William Noble (University of New England, Australia) and Stuart Gatehouse (MRC Institute of Hearing Research, Scotland) (Gatehouse & Noble, 2004; Noble & Gatehouse, 2004). The SSQ was later modified specifically for parents, for children, and for teachers by Karyn Galvin (The University of Melbourne, Australia) (Galvin & Noble, 2013). The listening scenarios in SSQ-P can be accessed at this link:https://links-lww-com.ezproxy.its.uu.se/EANDH/A212. In a Nordic collaboration the SSQ-P was translated into Sami, Norwegian, Swedish, and Finnish. The Swedish version of SSQ-P was translated, and back-translation comparisons were conducted by Elsa Erixon (Uppsala University), Elina Mäki-Torkko (Örebro University) and Ulrika Löfkvist (Uppsala University). A professional translator performed the back ...